Prospects of Philippine migration - Edita A. Tan (University of the Philippines, School of Economics (UPSE), 2019)
The paper briefly surveys recent migration policies in major destinations of Filipino migrants and tries to see their effect on migration flows in the past two decades. Most Western OECD economies have heightened their restrictive immigration programs that covered not only those relating to workers but also those for family unification. Their admission for employment is restricted to the highly skilled/highly educated labor. Despite the tightening of policy, emigration to Western OECD increased in the past three decades. Emigration to the US has been declining but emigration to other countries, though relatively small, rose. Saudi Arabia, the largest employer of foreign workers in the Gulf adopted the Nitaqat policy of imposing higher national to foreign labor ratio in the private sector. This may explain the drop in the flow of labor to the GCC in 2015 and 2016. The drop could be a temporary fluctuation as the state could not easily develop sufficient number of skilled and disciplined citizens to replace foreign labor. The GCC states' heavy dependence on foreign labor is expected to continue. The skill composition of foreign workers may change depending on their future economic and social development.
Keywords: J08; J15; J61; 330; migration; Philippines